THE NEEDS OF HIGH SCHOOL GIFTED CURRICULUM - Baldridge, Gregory (Acta Scientiae et Intellectus, 2024)
The development of high quality curriculum is a shared vision between educators, administrators, and developers, and, as a result, large publishers, school districts, and individual teachers develop disparate curriculums. To make things more complicated, the curricular needs of gifted learners differ from those in general education settings - a point that is especially true in high school science classes. Science curriculum is particularly poised to meet the unique needs of gifted learners. The sciences can provide many opportunities including greater depth and complexity and/or accelerated materials.